Pierre Auguste Renoir - Pach, Walter, 1883-1958.; Renoir, Auguste, 1841-1919.; Harry N. Abrams, Inc. (New York : Harry N. Abrams, Publishers, 2003)
This volume presents a survey of the life and works of French artist Pierre-Auguste Renoir (1841-1919) who was a leading painter in the development of the Impressionist style. The warm, sensuous painting of Auguste Renoir was throughout his long life the art of a man on good terms with the world
Pierre Auguste Renoir / Walter Pach -- Plates -- Frontispiece: Self-portrait -- Ballet dancer -- Portrait of Victor Chocquet -- Paul Durand-Ruel -- Stairway, Algiers -- Lady with a fan -- Gabrielle in an open blouse -- Judgment of Paris -- Girl with a mandolin -- Mademoiselle Romaine Lacaux -- Spring bouquet -- Diana -- Pont Neuf -- Madame Monet lying on a sofa -- Loge -- Mother and children -- Two little circus girls -- Madame Henriot -- Moulin de La Galette -- Girl reading -- Nude in the sunlight -- Portrait of a girl -- Seine at Asnieres ("the skiff") -- Madame Charpentier and her children -- Oarsmen at Chatou -- Umbrellas -- On the terrace -- Her first evening out -- Nude -- Luncheon of the boating party -- Fruits from the Midi -- Charles and Georges Durand-Ruel -- Dance at Bougival -- Girl with a straw hat -- Bathers -- Mother and child -- After the bath -- Girl wiping her feet -- In the meadow -- Two girls at the piano -- Gabrielle with Jean and a little girl -- Three bathers -- Anemones -- Reclining nude -- Woman at the fountain -- Gabrielle in a red blouse -- Shepherd boy -- Madame Tilla Durieux -- Woman with a mandolin.
"Masters of art."
Keywords: Renoir, Auguste, -- 1841-1919 -- Criticism and interpretation; Impressionism (Art) -- France